Pemodelan Bangkitan Pergerakan pada Perumahan Griya Citra Asri Kota Surabaya - Kurnia Hadi Putra; Muhammad Reza Fikma Effendi (Jurnal Teknik Sipil, 2020)
As an industrial city in west Surabaya exactly Margomulyo industrial area, Surabaya city has numerous housings to support people’s needs such as Griya Citra Asri (GCA) residence. Consequently, the road performances are decreasing and eventually disrupt the activities and movement for both humans and goods from inside and outside the town, for instance traffic congestion, accident, and limited vehicle speed which does not meet the speed plan.  Therefore, this research aimed at investigating the characteristics of trip among people living in this housing area. Besides, it was also intended for figuring out the model of trip generation of people at Griya Citra Asri Surabaya residence using multiple linear regression. The best model for movement generation obtained Y = -0.808 + 0.156 + 0.083 + 0.166 + 0.665 + 0.165 + 0.170 + 0.091 having R2 = 0.997, F count = 9966700, in which X1 = total family members, X2 = total revenue, X3 = total family members who are working,  X4 = total family members who are schooling, X5 = total vehicles, X6 = total cars, and X7 = total travel distances. Accordingly, there were 2 dominant factors affecting the trip generation at Griya Citra Asri Surabaya housing namely total family members who are schooling (X4) and total cars (X6).